THE ROLE OF WOMEN IN EDUCATION AS SEEN IN THE FILM MONA LISA SMILE DIRECTED ED BY MIKE NEWELL - Delia Mamonto; Stephani Johana Sigarlaki; Arter J. Senduk (Universitas Sam Ratulangi, 2026)
This research analyzes the role of women in education as represented in the film Mona Lisa Smile (2003) directed by Mike Newell. The study aims to identify the traditional roles imposed on women in the 1950s and to examine how these roles are constructed through cinematic representation. This research applies feminist theory, particularly Betty Friedan’s concept of The Feminine Mystique and Stephanie Coontz’s analysis of postwar domestic ideology, to explore how women’s education was directed toward marriage and domestic fulfillment rather than intellectual independence or professional careers. In addition, Mario Klarer’s film theory, especially the spatial and acoustic dimensions, is used to analyze how visual composition, classroom space, and sound elements reinforce gender expectations. This study employs a descriptive qualitative method, using dialogues and selected scenes as primary data supported by relevant academic sources. The findings reveal several traditional educational roles, including educated companion, intelligent homemaker, consumerism agent, pressure to abandon education for marriage, decline of professional ambition, and sex-directed curriculum. The research concludes that the film critiques restrictive gender norms while simultaneously presenting education as a potential space for women’s resistance, self-awareness, and empowerment.